Desenvolvimento de uma plataforma para estudo de retificador tiristorizado em malha fechada - Queiroz, Winner Zavolski (2022)
Different topologies of Retificator circuits using SCR's (Silicon Controlled Rectifiers) have applications in industrial processes such as DC motor drive, plasma generation, and electroplating, among others. In this work, it is proposed the triggering of thyristors using a closed loop control in order to maintain the output voltage of the converter constant. In addition, the platform developed is a didactic tool for teaching and research in the areas of control systems and power electronics. The designed platform is composed of a current sensor, a signal conditioning circuit to evaluate the system response, an optical isolation circuit, and a microcontroller to board control algorithms for closed-loop operation. During the work, the schematics of all proposed circuits are presented, as well as the modeling of plant dynamics via computer simulation and the control system design for digital implementation.